Fitting EMC structure functions with intrinsic charm - Rottoli, L (Scuola Internazionale Superiore di Studi Avanzati (S I S S A), 2016)
A detailed study of the impact of the data collected by the European Muon Collaboration (EMC) on the parton distribution function (PDF) of the charm quark is presented. The analysis is performed in the NNPDF framework, and the charm PDF is freely parametrized on equal footing as light quark and gluon distributions. We find that variations in the treatment of EMC data do not modify the charm PDF and do not affect our previous conclusion on the presence of an intrinsic component in the charm PDF.